Managing Zakat Funds through Technological Integration: A Case Study of MyIPIZ Grants System for Institute of Research and Zakat Innovation (IPIZ) at Universiti Utara Malaysia (UUM) (Architecture Image Studies, 2025)
This paper explores the integration of digital technologies in managing Zakat-funded research grants through a case study of the MyIPIZ Grants System developed by the Institute of Research and Zakat Innovation (IPIZ) at Universiti Utara Malaysia (UUM). Zakat institutions serve as vital catalysts for economic development and community empowerment by allocating funds toward research and innovation initiatives; however, they frequently face challenges such as manual inefficiencies, limited transparency, and inadequate mechanisms to assess the socio-economic impact of these developmental investments. The MyIPIZ Grants System addresses these issues by applying principles of Business Process Reengineering (BPR) and stakeholder theory to automate and optimise the grant management lifecycle, from application submission to final reporting. It employs digital workflow encompassing online applications, automated approvals, fund disbursement, real-time monitoring, and comprehensive digital reporting. This transformation enhances efficiency, ensures compliance with Shariah principles, and promotes stakeholder trust through improved accountability and transparency. The study also identifies key implementation challenges such as user resistance, integration issues, and data security concerns, and recommends strategies including stakeholder engagement, capacity building, and leveraging latest technologies. Lessons from MyIPIZ's implementation underscore its potential as a replicable model for other Zakat institutions aiming to modernise their fund governance. Ultimately, this research contributes to the broader discourse on Islamic financial digitalisation by offering a practical and ethically grounded framework for Zakat fund administration in the digital era.